Комп’ютерне прогнозування підвищення ефективності доочистки води після застосування коагуляції у швидких багатошарових фільтрах - Бомба, Андрій Ярославович; Климюк, Юрій Євгенійович (НТУ "ХПІ", 2019)
Сформовано математичну модель для комп'ютерного прогнозування процесу доочистки води від багатокомпонентних домішок після застосування коагуляції у швидких багатошарових фільтрах конусоподібної форми при додержанні сталої швидкості фільтрування, що враховує дослідження зміни характеристик кусково-однорідних пористих завантажень, які володіють окислювально-відновними властивостями. Запропонована модель дозволяє шляхом проведення комп'ютерних експериментів дослідити зміну характеристик кусково-однорідних пористих завантажень, спрогнозувати оптимальні варіанти використання коагулянтів і фільтрувальних матеріалів, збільшення тривалості роботи швидких багатошарових конусоподібних фільтрів за рахунок вибору їх форми і висоти шарів з урахуванням граничнодопустимих норм по кожній компоненті багатокомпонентних домішок.

In the paper a mathematical model for computer predicting the process of water purification from multicomponent impurities after applying coagulation in rapid multilayer cone-shaped filters with the constant rate of filtration, which takes into account the changes in the characteristics of piecewise-homogeneous porous redox load, is formulated. Each layer of the load is characterized by its own coefficients of filtration, active porosity and diffusion of multicomponent impurities in the filtration flow, and the sediment adsorbed on the grains of the load. An algorithm for numerically-asymptotic approximation of solution of the corresponding nonlinear singularly perturbed boundary value problem for a model region of a conical shape, bounded by two equipotential surfaces and a flow surface, separated by some given equipotential surfaces into several subdomains, is developed. The proposed model allows to predict by computer experiments the change in the characteristics of piecewise-homogeneous porous loads, to determine the optimal variants of coagulants and filter materials, and to increase the durability of the rapid multilayer cone-shaped filters by choosing their shape and height of layers taking into account the maximum allowable standards for each component of multicomponent impurities.
Computer prediction of improving efficiency of water purification after coagulation in rapid multilayer filters
Keywords: математична модель; процес доочистки води; багатокомпонентна домішка; конусоподібна форма; mathematical model; multicomponent impurity; cone-shaped form